Computer hacking beginners guide : how to hack wireless network, basic security and penetration testing, Kali Linux, your first hack - Norman, Alan T. ([United States] : [publisher not identified], 2018)
This book covers the basics of everything you need to know about hacking.
CSE
Trim Education
Keywords: Computer security; Hacking; Computer programming; Computer science